1997
DOI: 10.1093/brain/120.9.1603
|View full text |Cite
|
Sign up to set email alerts
|

Phantom limbs in people with congenital limb deficiency or amputation in early childhood

Abstract: It is widely believed that people who are congenitally limb-deficient or suffer a limb amputation at an early age do not experience phantom limbs. The present study reports on a sample of 125 people with missing limbs and documents phantom experiences in 41 individuals who were either born limb-deficient (n = 15) or underwent amputation before the age of 6 years (n = 26). These cases provide evidence that phantom limbs are experienced by at least 20% of congenitally limb-deficient subjects and by 50% of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
8

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(131 citation statements)
references
References 3 publications
2
121
0
8
Order By: Relevance
“…This idea of a hardwired blueprint is not Table 2 Dreaming about the body as before the amputation (n = 45) Dreaming about the body as after the amputation (n = 30) new. Melzack, Israël, Lacroix, and Schultz (1997) discussed phantom limb sensations in subjects born without limbs. They argued that the basic experience of the body is not solely based on information pathways fed by sensory input, but that the body image is determined also partly by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This idea of a hardwired blueprint is not Table 2 Dreaming about the body as before the amputation (n = 45) Dreaming about the body as after the amputation (n = 30) new. Melzack, Israël, Lacroix, and Schultz (1997) discussed phantom limb sensations in subjects born without limbs. They argued that the basic experience of the body is not solely based on information pathways fed by sensory input, but that the body image is determined also partly by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…We are born with a full-blown potential for imaging body parts" (Abramson and Feibel 1981, p 99). In more moderate terms, a genetically built-in component for a body schema was described by Melzack (1990;Melzack et al 1997). According to this author, a widespread network of thalamocortical and limbic loops (the "neuromatrix") is basically innate, but continuously shaped during a person's life by sensory inputs and motor commands.…”
Section: Phantoms Of Congenitally Absent Limbs As Manifestations Of Amentioning
confidence: 99%
“…There is anecdotal evidence for phantom sensations being triggered by the observation of other people moving their limbs, both in cases of traumatic amputation (Henderson and Smyth 1948) and congenital limb deficiency (Melzack et al 1997). A woman born without arms and legs described how visually observing her sister's movements could evoke feeling these movements as if they were her own: (Frank 1986, p 191) Extensive work with a woman born without forearms and legs (AZ; 44 years old at the time of testing; see Fig.…”
Section: Phantoms Of Congenitally Absent Limbs As Manifestations Of Tmentioning
confidence: 99%
“…accident); 100% of these amputees report phantom sensations (Ritchie, 1980; Krane and Heller, 1995), while 83-100% experience phantom pain (Krane and Heller, 1995; Ritchie, 1980, respectively). More recently, Melzack et al (1997) reported that phantoms were experienced by 33% of individuals who were either born without alimb (12%) or underwent surgical amputation prior to 6 years of age (21%). Several attempts have been made to formulate a theoretical basis for phantom sensations and phantom pain.…”
Section: Introductionmentioning
confidence: 99%